Water and thermal needs of green maize in the Submédio Vale do São Francisco (Research, Society and Development, 2020)
Considering the knowledge of the water requirement of the crop contributes to efficient irrigation planning and, for each physiological subperiod, plants require a certain amount of heat, the objective of this study was to determine the water and thermal needs of maize grown under the climatic conditions of the Submédio do Vale do São Francisco. The research was conducted from September to December 2018 in the experimental area of DTCS/UNEB in Juazeiro, BA. The cultivars used were BRS Caatingueiro and BRS Assum Preto. The crop evapotranspiration (ETc) was obtained through daily readings in evapotranspirometers and the reference evapotranspiration (ETo), obtained by the Penman-Monteith method. The crop coefficient was determined by the equation Kc = ETc / ETo. The degrees-day was determined by the difference between the average air temperature and the lower base temperature (10 ° C). For the whole crop cycle, BRS Caatingueiro presented mean ETc of 6.5 mm, Kc of 1.13 and 1300.7 GD, to BRS Assum Preto, ETc of 7.1 mm, Kc of 1.23 and 1348.2 GD. For the climatic conditions of the Submédio do Vale do São Francisco, the water consumption of crop BRS Caatingueiro was 451.9 mm for crop BRS Assum Preto, 509.7 mm. In stage III, the climatic condition was decisive to increase the water consumption of crop BRS Caatingueiro by 10.7%, compared to crop BRS Assum Preto. The monitoring of climatic conditions in loco is crucial for correct estimates of water consumption of crops.